2007
DOI: 10.1007/s10856-007-3297-x
|View full text |Cite
|
Sign up to set email alerts
|

3D-Cultivation of bone marrow stromal cells on hydroxyapatite scaffolds fabricated by dispense-plotting and negative mould technique

Abstract: The main principle of a bone tissue engineering (BTE) strategy is to cultivate osteogenic cells in an osteoconductive porous scaffold. Ceramic implants for osteogenesis are based mainly on hydroxyapatite (HA), since this is the inorganic component of bone. Rapid Prototyping (RP) is a new technology in research for producing ceramic scaffolds. This technology is particularly suitable for the fabrication of individually and specially tailored single implants. For tissue engineering these scaffolds are seeded wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 15 publications
3
47
2
Order By: Relevance
“…A similar route was used to produce a polymer-TCP scaffold. Similar results, with the same approach, were obtained also in other works [55,56]. Pore diameters of ∼340 mm have been obtained; shrinkage and compressive mechanical properties have been analyzed.…”
Section: Ballistic Technologysupporting
confidence: 83%
“…A similar route was used to produce a polymer-TCP scaffold. Similar results, with the same approach, were obtained also in other works [55,56]. Pore diameters of ∼340 mm have been obtained; shrinkage and compressive mechanical properties have been analyzed.…”
Section: Ballistic Technologysupporting
confidence: 83%
“…Calcium magnesium silicate induced proliferation and expression of ALP and OC in vitro [46]. hMSCs on HA had excellent osteoinduction [47], and porous HA scaffolds showed an enhancement of BMSC differentiation [48]. However, sintered HA implants are generally not resorbable.…”
Section: Discussionmentioning
confidence: 99%
“…However, ex vivo matrix mineralization assays lack specificity, may be confounded 1 by simple precipitation of calcium phosphate, and exhibit a surprisingly poor concordance with the cellular capacity to form bone in vivo. [2][3][4] To overcome such problems, several investigators have established 3D culture system for osteoblastic cells [5][6][7][8][9] and reported induction of better osteoblast differentiation compared to 2D culture. 10,11 However, most of the described 3D culture studies, certainly those using osteogenic cells derived from osteosarcoma cell lines, did not use bone formation as their final outcome and employed instead a modified form of ex vivo mineralization assay.…”
Section: Introductionmentioning
confidence: 99%